Permasalahan dari Adanya Ketidaksesuaian Harga yang Tertera Pada Transaksi Akta Jual Beli (AJB) dengan Harga Transaksi Sesungguhnya - Kurniawan, Stanley; Djaja, Benny (UNES Law Review, 2023)
In transferring rights to land and buildings by way of sale and purchase, the requirements for the formation of an agreement are sufficient based on the agreement between the parties and an agreement. Article 1320 of the Civil Code explains the conditions for the validity of an agreement. In the process, the transfer of land rights is carried out by prioritizing the principles of light and cash, if an agreement has a defect in the subject, the agreement can be canceled, while there is a defect in the object, it is null and void. PPAT plays an important role as an authorized official in making a Sale and Purchase Deed, in this case PPAT is responsible for the product it has made and its making must be in accordance with applicable laws and regulations. If a PPAT commits an act that is not in accordance with the applicable regulations, there are legal consequences that will become a problem in the future. The type of research used is normative. To support this research, the author uses a literature study type of research, which examines several documents related to this research. The method in this research is a normative method with a statutory approach. The research data shows how the problem of the price discrepancy in the Sale and Purchase Deed with the actual price.